2021
DOI: 10.3390/biom11030445
|View full text |Cite
|
Sign up to set email alerts
|

Agroindustrial Wastes as a Support for the Immobilization of Lipase from Thermomyces lanuginosus: Synthesis of Hexyl Laurate

Abstract: As a consequence of intense industrialization in the last few decades, the amount of agro-industrial wastes has increasing, where new forms of valorization are crucial. In this work, five residual biomasses from Maranhão (Brazil) were investigated as supports for immobilization of lipase from Thermomyces lanuginosus (TLL). The new biocatalysts BM-TLL (babaçu mesocarp) and RH-TLL (rice husk) showed immobilization efficiencies >98% and hydrolytic activities of 5.331 U g−1 and 4.608 U g−1, respectively, agains… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…by using cross-linking on the magnetic particles as a support and found that it has applications in the synthesis of 2-phenylethyl butanoate (fragrance compound and flavor). Lira et al (2021) also immobilized the lipase of Thermomyces lanuginosus on agro-industrial wastes as a support and found that it has applications in the production of hexyl laurate.…”
Section: Immobilization Of Fungal Lipasementioning
confidence: 99%
“…by using cross-linking on the magnetic particles as a support and found that it has applications in the synthesis of 2-phenylethyl butanoate (fragrance compound and flavor). Lira et al (2021) also immobilized the lipase of Thermomyces lanuginosus on agro-industrial wastes as a support and found that it has applications in the production of hexyl laurate.…”
Section: Immobilization Of Fungal Lipasementioning
confidence: 99%
“…Various value‐added materials can be produced from agricultural residues, such as industrially important enzymes (Ravindran et al, 2018). An alternative for this biomass is their use as a carrier for the immobilization of enzymes and cells (Bilal et al, 2017; Bilal & Iqbal, 2019; Dutta & Wu, 2014; Girelli et al, 2020; Li et al, 2019; Lira et al, 2021; Rodríguez‐Restrepo & Orrego, 2020). The lignocellulosic materials fulfill the specific properties (inertness, physical strength, stability, renewability, and low cost) of a support on which a biocatalyst can be fixed (Rodríguez‐Restrepo & Orrego, 2020).…”
Section: Agricultural Residual Biomass Utilizationmentioning
confidence: 99%